Comparative evaluation of three peripheral intravenous catheter designs for intensive blood sampling in Phase I clinical trials: A prospective quasi-experimental comparative study - Shulong Ding; Tianchun Zhou; Shiyun Gu; Xiaoqian Liu; Sijia Yu; Lu Chen; Mengting Ji (The Journal of Vascular Access, 2026)
Background: Intensive serial blood sampling is critical for pharmacokinetics (PK) in Phase I trials but elevates pre-analytical hemolysis risks. While peripheral intravenous catheters (PIVCs) minimize needle trauma, evidence regarding device design remains inconsistent, potentially owing to unstandardized pre-analytical techniques across diverse clinical settings. This study introduced a rigorous evidence-based standard operating procedure (SOP) to minimize operational variability, aiming to clarify the respective, independent contributions of PIVC configurations versus temporal dynamics to specimen integrity. Method: In this single-center, prospective quasi-experimental comparative study, 246 healthy subjects ( n = 82 per group) were allocated in a 1:1:1 ratio to 20 G straight-type, Y-type, or single-port PIVCs for nine serial timepoints over 12 h. All cohorts followed an evidence-based pre-analytical SOP featuring controlled tourniquet times, dead-space clearance, and low-pressure manual aspiration. Endpoints included specimen hemolysis, catheter occlusion, and re-cannulation rates. For the primary hemolysis endpoint, laboratory assessment was performed using coded specimens without catheter-group information provided to laboratory personnel. Results: Across 2194 PIVC specimens, the overall hemolysis rate was 2.01% (44/2194), with no statistically detectable differences among straight-type (2.06%), Y-type (1.92%), and single-port (2.03%) cohorts ( p = 0.98). Firth’s longitudinal regression detected no independent device effect ( p = 0.77); compared with straight-type, the odds of hemolysis were not statistically different for Y-type (OR = 0.82, 95% CI: 0.24–2.81) or single-port (OR = 0.65, 95% CI: 0.18–2.39) designs. Hemolysis incidence varied by sampling time, with the highest observed rate at the Pre-dose 1 h sampling point (6.10%, 15/246). Conclusion: Under a rigorous evidence-based SOP, catheter configuration was not associated with statistically detectable differences in hemolysis or functional failure during intensive PK sampling. Quality control systems should prioritize procedural standardization over equipment selection. Further multicenter validation is needed before catheter- or time-specific sampling strategies are recommended.